Grupos florísticos e suas relações ambientais na vegetação sazonalmente seca da caatinga, nordeste da América do Sul - Silva, Augusto César da (2018)
Aim Biogeographical regionalizations are representations of the organization of organisms in the geographical space in function of the various biotic to abiotic factors to past or present. Our aim was to propose a vegetacion bioregionalization of Caatinga based in floristic data, identifying the factors main that determine the grups distribuition patterns. Location Caatinga phytogeographical domain Methods To carry out the floristic bioregionalization of the caatinga. We compiled 260 floristic inventories that compose the "Caaporã" database. Floristic inventories were used to construct a species matrix by site, and we used sorting and grouping techniques to identify the number of floristic groups in the Caatinga. We applied an interpolation method to map compositional variation axes throughout the Caatinga extension and then classified compositional dissimilarity according to the number of floristic groups identified a priori. In addition, we did a UPGMA to verify the relationship between floristic groups. We used multinomial logistic regression models with AIC and wAICc criteria to investigate the current climatic influence, topographic complexity, historical climate changes and human footprint in the explanation of the groups. Results We identified a total of 2666 species of plants organized into nine floristic groups, some are distributed latitudinally (North-South), while others are restricted to certain specific regions in the southern and western portions of the domain. The results of the multinomial regression show that the aridity index (AI) individually was the variable that best explains the distribution pattern of the groups. Therefore the variation in water conditions was the significant model that best describes the distribution pattern of the groups. The models evaluating soil, topography and historical variables were not significant. Main Conclusions The distribution pattern of the Caatinga biogeographic groups was shown to be largely determined by aridity. Due to its climatic variability and instability throughout the domain it is possible that many of the floristic groups present in the Caatinga are composed of groups of species from the Atlantic Forest, the Cerrado or even the Amazon. Overall, the regionalization of the Caatinga into floristic groups provides a cohesive spatial representation of the biogeographic distributions in the Caatinga. Therefore, our proposed classification together with the other suggestions contribute to a better understanding of the floristic distribution patterns of the caatinga and the processes that govern these floristic groups.